Comparing the Local Climate Change and its Effects on Physiological Aspects and Yield of Ramie Cultivated in Different Biophysical Environments - Subandi , M (Asian Journal of Agriculture and Rural Development, 2014)
Three experiments in three different biophysical environments were conducted in Jatinangor, Sumedang District, Jatitujuh. Majalengka District and Bandung District of West Java Province, Indonesia. The experiment were conducted to evaluate the environments, seasons, manure, nitrogen and potassium effect on the physiological aspects and yield of ramie plant (Boehmerianivea L. Gaud).The locations diverse at different elevation, rainfall type and soil type and atmospheric regimes. The experiments passed the years 2000-2001. The experiment in Sumedang regency was continued with two other experiments in 2007, and experiment in Bandung district was conducted in 2014.The field experiments design used in all the locations were randomized block design arranged in factorial pattern with two factors and two replications. Climatic analysis is done by comparing the atmospheric data of 2000-2001 and the data of 2002-2007 and the data of 2014. Assumed that all the local atmospheric data are atmospheric data under influence of climatic global change. Results of the experiments were: Jatitujuh region is not suitable for ramie cultivation. Dosage of waterw3=35%-40% of Field Capacity affecting sufficient growth on plant.The minimum dosage at which plant survive to produce yield is representing the most efficient input of production.Water supply for ramie plant could be designed to the most efficient volume to maintain the need of metabolism.